(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
In this paper Dr. B.R. Ambedkar’s critical views on the caste systems and his vision for social justice in India are discussed. It charts the historical roots of caste and the socio-economic implications arising from it by examining Ambedkar’s arguments against caste discrimination as they appear in Annihilation of Caste. It brings to light Ambedkar’s work advocating for the margins through education, the economy and politics. It analyses his role in embedding into the Indian constitution the principles of liberty and equality and fraternity, for example through abolition of untouchability and affirmative action. In addition, the paper assesses the transformative potential of Ambedkar’s ideas for Dalit rights and the lasting significance of his thinking for contemporary campaigns in favour of caste equity and social justice. At the same time that enormous progress has been made in forestalling caste based injustice, systemic discrimination remains entrenched, and thus the importance of the vision that Ambedkar bequeathed to India in 1956 remains apt. The study strives to reaffirm that addressing caste based oppression is important in light of his philosophy and reforms by providing an in depth analysis of the philosphy, and reforms.